Pemberdayaan Ibu-Ibu Rumah Tangga Melalui Penyuluhan Inovasi Produk Dan Pemasaran Online Kerupuk Lontong Di Dusun Blandongan Desa Ngawi Kecamatan Ngawi Kabupaten Ngawi - Clerency Ardiva Putri; Dwi Setya Nugrahini (IAI Darussalam, 2021)
Innovation can be defined as the process or result of developing and utilizing knowledge, skills (including technological skills) and experience to create and improve products and processes so that they provide added value. Lontong is a mainstay food that is widely traded by the people of Dusun Blandongan. So do not be surprised if the average woman from Dusun Blandongan Ngawi works as a rice cake seller. To empower their assets, namely lontong food, KPM-DDR students will conduct counseling on product innovation and online marketing of lontong crackers. This activity aims to innovate products and provide marketing information for lontong sellers and housewives to get additional income when at home and to increase competitiveness, promotion and marketing of local food products for the people of Dusun Blandongan Ngawi. Regarding the method used for the counseling, the researcher uses the Asset-based community development (ABCD) approach, which is more appropriate for KPM-DDR. The results of the counseling are, 1) Extension activities and training on making rice cake crackers with housewives went well; 2) In the online media counseling that is used to market the product, the Facebook and Whatsapp applications are chosen because many residents have often operated the two applications.